2014
DOI: 10.1007/s10120-014-0431-6
|View full text |Cite
|
Sign up to set email alerts
|

A newly modified esophagogastrostomy with a reliable angle of His by placing a gastric tube in the lower mediastinum in laparoscopy-assisted proximal gastrectomy

Abstract: The modified EG technique has advantages over the JI technique because of its simplicity and low incidence of residual food and bile reflux. The next step would be to explore this technique further by a prospective multi-institutional study to confirm the reproducibility of its benefits. Miniabstract: The modified EG technique has advantages over the JI technique because of its simplicity, high rate of laparoscopy use, and low incidence of gastroesophageal reflux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 20 publications
1
45
1
1
Order By: Relevance
“…Postoperative anastomotic stricture is another possible complication of proximal gastrectomy, especially after oesophagogastrostomy. Oesophagogastric anastomotic stricture occurred in 8 per cent of the patients, a lower rate than that reported in most other studies (range 8·2–28·0 per cent).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Postoperative anastomotic stricture is another possible complication of proximal gastrectomy, especially after oesophagogastrostomy. Oesophagogastric anastomotic stricture occurred in 8 per cent of the patients, a lower rate than that reported in most other studies (range 8·2–28·0 per cent).…”
Section: Discussioncontrasting
confidence: 57%
“…Surgical outcomes of LPG may depend on the type of reconstruction, as reflux oesophagitis is one of the most important determinants of long‐term outcome. The size of the remnant stomach may influence other long‐term outcomes, such as haemoglobin concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Simple EG without any additional antireflux procedure has been reported to cause reflux esophagitis in 9.1%‐35.3% of patients, and even JI, JPI and DT, which are supposed to prevent the occurrence of reflux, resulted in reflux esophagitis in 0%‐15.8%, 8.3%‐15.8% and 0%‐25% of cases, respectively, which are not negligible incidences . Some EG with additional antireflux procedures, such as fundoplication, successfully reduced the incidence of reflux esophagitis to below 10%, whereas other EG failed to prevent the occurrence of reflux even with additional antireflux procedures, resulting in reflux esophagitis in over 30% of cases . Previous DFT reports that included a variety of cases (n = 112) showed that DFT successfully prevented the occurrence of reflux esophagitis (≥grade B) with an incidence of 2.7% (3/112) .…”
Section: Discussionmentioning
confidence: 99%
“…The reasons why on -third of patients with a T1 U tumor received total gastrectomy in our institute may be related to this problem. Recently, we and others developed novel methods for modified esophagogastrostomy by creating a reliable angle of His using a stapler [26,27]. These techniques may become a feasible choice for simple reconstruction after proximal gastrectomy.…”
Section: Discussionmentioning
confidence: 99%